Appropriate and effective management of rheumatoid arthritis. Issue 6 (12th May 2004) - Breedveld, F C; Kalden, J R
Abstract : Early referral (at <3 months) and early DMARD treatment enable the course of RA to be changed. Once the disease has become aggressive it is much harder to treat and improvements will not be as great as they would have been with earlier treatment. The latest strategies and treatments enable remission to be achieved in many more patients than formerly.